Assessment of the state of crops in the territory of the Chelyabinsk Research Institute of Agricultural Sciences based on remote sensing data - Gusev A.S.; Inysheva V.A.; Lopukhov P.M.; Anisimov Yu.B.; Bronitskaya S.A. (BIO Web of Conferences)
In the context of climate change and increasing food demand, it is important to optimize agricultural production processes. Remote sensing allows to quickly and accurately assess the condition of crops, which contributes to more efficient management of land resources. The use of satellite data provides wide coverage and allows to obtain up-to-date information in large volumes in a short time, which is an effective tool in planning agronomic activities and forecasting crop yields. This article analyzes the current state of crops using the example of agricultural land in the Chelyabinsk Research Institute of Agricultural Sciences using remote sensing methods, namely, the use of the NDVI (Normalized Difference Vegetation Index) as an increment of the assessment. Despite some limitations related to the influence of external factors and the accuracy of data, the use of NDVI in combination with other monitoring methods opens up new opportunities for increasing agricultural productivity and sustainability in the current environment.